74.6k views
0 votes
Without using a calculator show that (49/16) raised to the power of negative 3/2 equals 64/343

show all steps ​

User Itay Oded
by
5.5k points

1 Answer

1 vote

Answer:

Explanation:

Apply exponent rule
a^(-b)=(1)/(a^b):


\implies \left( (49)/(16) \right) ^{-{\frac32}}=(1)/(\left( (49)/(16) \right) ^(\frac32))

Apply exponent rule
\left( (a)/(b) \right) ^c=(a^c)/(b^c):


\implies (1)/(\left( (49)/(16) \right) ^(\frac32))=(1)/(\left( (49^(\frac32))/(16^(\frac32)) \right) )

Factor the 49 and 16:


\implies (1)/(\left( (49^(\frac32))/(16^(\frac32)) \right) )=(1)/(\left( ((7^2)^(\frac32))/((4^2)^(\frac32)) \right) )

Apply exponent rule
(a^b)^c=a^(bc):


\implies (1)/(\left( ((7^2)^(\frac32))/((4^2)^(\frac32)) \right) )= (1)/(\left( (7^3)/(4^3) \right) )=(1)/(\left( (343)/(64) \right) )

Apply fraction rule
(1)/((a)/(b))=(b)/(a)


\implies (1)/(\left( (343)/(64) \right) )=(64)/(343)

User Kim Morrison
by
5.7k points